Comparison of Two Simple Power Plant Design at Different Height and Water Discharge - Ariani, Tri; Gumay, Ovilia Putri Utami (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
This study aims to determine the comparison of two electrical energy produced by the Minihidro Power (PLTMH) at differentheights and water discharge. After all the systems that support the construction of the mini-hydro have been designed andconnected to each other to form the expected mini-hydro system, the next step is the mini-hydro work testing phase. As for theimplementation using the experimental method by operating a mini-hydropower plant with variations in changing the heightand water discharge. This research was conducted to determine the current and voltage produced by observing the current andinput voltage and current and output voltage of the inverter circuit. The test is carried out using ammeters and voltmeters, thenthe measurement results are entered in a table. This study obtained data V and me to calculate the electric power generated(P). The analysis was done descriptively by comparing the data obtained to observe the effect of water height (h) and waterdischarge (Q) on electric power (P). From the experimental results, the greater the price of h and Q, the greater the Pproduced. So from this experiment, we can be implemented in a PLTMH builder by knowing the maximum water level anddischarge from a water source. From the results of these experiments it can be said the higher the water to the generator, thegreater the electrical energy produced. This is in accordance with the potential energy it has. The greater the potential energy ofan object means the greater the electrical energy. From the comparative data of Experiments 1 and 2, it is obtained that theamount of water debit greatly influences the amount of energy/electricity generated. This is due to the large mass of water thatwill hit the turbine so the generator turns faster, resulting in large mechanical energy. So to build a PLTMH, water flow andaltitude must be considered.